Comparison of a quantum random number generator with pseudorandom number generators for their use in molecular Monte Carlo simulations. Issue 31 (18th September 2017) - Ghersi, Dario; Parakh, Abhishek; Mezei, Mihaly
Abstract : Four pseudorandom number generators were compared with a physical, quantum‐based random number generator using the NIST suite of statistical tests, which only the quantum‐based random number generator could successfully pass. We then measured the effect of the five random number generators on various calculated properties in different Markov‐chain Monte Carlo simulations. Two types of systems were tested: conformational sampling of a small molecule in aqueous solution and liquid methanol under constant temperature and pressure. The results show that poor quality pseudorandom number generators produce results that deviate significantly from those obtained with the quantum‐based random number generator, particularly in the case of the small molecule in aqueous solution setup. In contrast, the widely used Mersenne Twister pseudorandom generator and a 64‐bit Linear Congruential Generator with a scrambler produce results that are statistically indistinguishable from those obtained with the quantum‐based random number generator. © 2017 Wiley Periodicals, Inc. Abstract : Four pseudorandom number generators were compared with a physical, quantum‐based random number generator using the NIST suite of statistical tests. We then measured the effect of the five random number generators on various calculated properties in different Markov‐chain Monte Carlo simulations. The results show that poor quality pseudorandom number generators produce results that deviate significantly from those obtained with the quantum‐based random number generator. In contrast, the Mersenne Twister pseudorandom generator and a 64‐bit Linear Congruential Generator with a scrambler produce results that are statistically indistinguishable from those obtained with the quantum‐based random number generator.